A Relational Realist Vision for Education Policy and Practice - Adi, Basem (Open Book Publishers, 2023)
This volume argues that relational realism can help us to make better educational policy that is more effective in practice. Basem Adi draws on critical realism to thoroughly re-examine fundamental assumptions about how government policymaking works, developing an ontological basis from which to examine existing government approaches and imagine an alternative approach based on a relational realist-informed critical pedagogy. Adi casts familiar issues in a new light by drawing on a less familiar theoretical and meta-theoretical tradition, offering a critique that can be productively engaged with by many educational organizations to tackle the issues they face. A Relational Realist Vision for Education Policy and Practice will be of great interest to academics of sociology, critical realism, sociological theory and education, as well as policymakers and educators seeking a theoretical perspective on their work.